Edukasi Kewirausahaan dan Praktik Pembuatan Keychain dari Mikroplastik di SD Negeri Grabag - Utami, Esti Margiyanti; Dewi, Anisa; Wati, Kurnia; Sagita, Mayka Nur; Yuniati, Diah (LPMP Imperium, 2026)
The problem of plastic waste that is difficult to overcome in the surrounding environment is a real challenge for the community. Through the Real Work Lecture (KKN) service program at SD Negeri Grabag, namely Education (Entrepreneurship Education) and the Practice of Making Keychains from Microplastics, this activity aims to foster an entrepreneurial spirit while increasing awareness of the use of microplastic waste through handicraft-based entrepreneurship education. The implementation method is carried out with a participatory approach, involving students directly in all stages of making keychains made of microplastics and resins, starting from design design, material mixing, printing, to product completion. The activity partners are Grabag State Elementary School students, with success indicators in the form of active involvement of participants, the ability to produce products that are suitable for sale, and an understanding of basic concepts of entrepreneurship. The results of the activity show that students gain real experience about the production process as well as an introduction to entrepreneurial concepts, such as creativity, precision, discipline, cooperation, and responsibility for the work. The impact of this activity not only increases students' practical skills and creativity, but also fosters concern for the environment through the use of microplastic waste into products with useful and economic value. Thus, this service program contributes to the formation of early entrepreneurial character as well as environmental awareness from elementary school age.